2018
DOI: 10.1007/s12551-018-0475-7
|View full text |Cite
|
Sign up to set email alerts
|

Building a dendritic actin filament network branch by branch: models of filament orientation pattern and force generation in lamellipodia

Abstract: We review mathematical and computational models of the structure, dynamics, and force generation properties of dendritic actin networks. These models have been motivated by the dendritic nucleation model, which provided a mechanistic picture of how the actin cytoskeleton system powers cell motility. We describe how they aimed to explain the self-organization of the branched network into a bimodal distribution of filament orientations peaked at 35°and − 35°with respect to the direction of membrane protrusion, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 82 publications
3
17
0
Order By: Relevance
“…Neither the WAVE complex nor Ena/VASP proteins are essential in the stretch-induced tip actin polymerization. These relationships are in agreement with the force-velocity relationship predicted by the BR mechanism although the results do not distinguish among BR models predicting similar exponential force-velocity curves (Mogilner & Oster, 1996, 2003Peskin et al, 1993) and more complex models incorporating the BR force-velocity relationship (Carlsson, 2003;Holz & Vavylonis, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…Neither the WAVE complex nor Ena/VASP proteins are essential in the stretch-induced tip actin polymerization. These relationships are in agreement with the force-velocity relationship predicted by the BR mechanism although the results do not distinguish among BR models predicting similar exponential force-velocity curves (Mogilner & Oster, 1996, 2003Peskin et al, 1993) and more complex models incorporating the BR force-velocity relationship (Carlsson, 2003;Holz & Vavylonis, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…The variations in the precise distribution of actin filament orientations at the cell edge, and the non-negligible presence of 3D orientations, are consistent with recent findings in the literature based on EM and modelling 4 . A range of angular distributions of actin filament orientations has been evidenced, which appears to be more complex and heterogeneous than a pure bimodal distribution with peaks positioned at the 70° branching angle 53 .…”
Section: Introductionsupporting
confidence: 90%
“…Adhesion of animal cells to the extracellular matrix is driven, for example, by dramatic conformational changes in force-sensing and force-transducing proteins such as integrins and talins. The precise geometry of actin filament assemblies 1,2,3,4,5 and its remodelling in space and time are further determinant for cell mechanics driving essential biological processes, including immune responses and tissue development. Thus, understanding the function of a protein and its interaction with its partners, necessitates that we observe its organization at the nanometer scale, both in position and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Gray lines: actin filaments; red: Arp2/3 complex; yellow:free barbed ends; orange: capped barbed ends; blue: free pointed ends. results (Holz and Vavylonis, 2018). Atilgan et al (Atilgan et al, 2005) reported that obtaining the ±35 • pattern requires restricting branching to occur primarily along the lamellipodium plane, which they attributed to structural constraints of the branching machinery at the leading edge.…”
Section: Planar Branching Along Lamellipodial Plane Sharpens the Filament Orientation Patternmentioning
confidence: 99%
“…This dendritic lamellipodia network structure, evident in electron micrographs of keratocytes (Svitkina et al, 1997) has been quantified by more recent electron tomograms near the leading edge, revealing the number of barbed ends, branches and filaments (Mueller et al, 2017;Vinzenz et al, 2012). Its characteristic pattern with filaments orientated primarily at ±35 • with respect to the protrusion axis (Koseki et al, 2019;Maly and Borisy, 2002;Mueller et al, 2017;Schaub et al, 2007) has been interpreted by two dimensional dendritic network models (Atilgan et al, 2005;Holz and Vavylonis, 2018;Maly and Borisy, 2002;Schaus et al, 2007;Weichsel and Schwarz, 2010).…”
Section: Introductionmentioning
confidence: 98%